Change in geomechanical properties of limestone due to supercritical CO2Injection - Zhang, Y.; Lebedev, Maxim; Sarmadivaleh, Mohammad; Barifcani, Ahmed; Iglauer, Stefan (2016)
© 2016 Society of Petroleum Engineers. All rights reserved. CO2geo-storage in deep saline aquifers or oil and gas reservoirs is a key technology to mitigate anthropogenic greenhouse gas emissions. Technically, CO2is captured from large emitters, e.g. coal-fired power plants, and injected deep underground into geological formations. In case of hydrocarbon reservoirs, this can be combined with CO2-enhanced petroleum recovery, which is rather efficient. One potential host rock for CO2is thus porous limestone; however, the geomechanical response (especially at the microscale) of the limestone when it is exposed to the acidic CO2-fluids (CO2saturated brine or wet supercritical CO2) is only poorly understood. We thus measured the geomechanical properties of Savonnières limestone cores before and after injection of supercritical CO2at the microscale. The CO2was injected at representative flow conditions: a fully brine saturated storage reservoir at approximately 1000m depth (323K temperature, 10 MPa pore pressure, 5 MPa effective stress) was simulated, and 10 pore volumes of supercritical CO2were injected at a capillary number of 10-6, which mimics storage conditions. The dynamic elastic properties and the formation factor were measured and compared with the geomechanical response. We found that the dynamic Young's modulus decreased, while permeability and porosity increased after scCO2injection; however, the micro-scale indentation moduli showed a dual behaviour: while the indentation modulus slightly increased in less consolidated rock areas, it decreased in the more and highly consolidated areas. We conclude that the scCO2injected into limestone weakens the well consolidated areas, but strengthens the weaker areas.